2010
DOI: 10.1093/eurheartj/ehq443
|View full text |Cite
|
Sign up to set email alerts
|

Impaired myocardial perfusion reserve and fibrosis in Friedreich ataxia: a mitochondrial cardiomyopathy with metabolic syndrome

Abstract: Patients with FA have abnormal myocardial perfusion reserve that parallels met-S severity. Impaired perfusion reserve and fibrosis occur in the absence of significant hypertrophy and prior to clinical heart failure, providing potential therapeutic targets for stage B cardiomyopathy in FA and related myocardial diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 37 publications
3
71
0
6
Order By: Relevance
“…1). As in our previous cohort, 6 increased triplet expansion correlated with greater RWT (r=0.37, P <0.05) (Table II) (Figs. 2 and 3).…”
Section: Picp Levels and Baseline Measures Of Left Ventricular Structsupporting
confidence: 83%
See 3 more Smart Citations
“…1). As in our previous cohort, 6 increased triplet expansion correlated with greater RWT (r=0.37, P <0.05) (Table II) (Figs. 2 and 3).…”
Section: Picp Levels and Baseline Measures Of Left Ventricular Structsupporting
confidence: 83%
“…5 Our group has previously shown that myocardial fibrosis can occur in FA patients who do not have overt cardiomyopathy. 6 As a measurement criterion for collagen production, PICP holds potential appeal; however, its usefulness in FA cardiomyopathy had not previously been evaluated. In our study, we have identif ied PICP as a marker of progressive LV dilation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The deficit in transcription of FXN in FRDA patients is often characterized by mitochondrial damage and the ensuing energy dysregulation (17,41). The central pathological outcomes of FRDA on the heart include hypertrophic cardiomyopathy, myocardial fibrosis, and myocardial infarction, which often progress the heart to congestive heart failure (38,39,53).…”
Section: New and Noteworthymentioning
confidence: 99%